Evidence for regulation of 3-hydroxy-3-methylglutaryl coenzyme A reductase activity and cholesterol synthesis in nonhepatic tissues of rat. - Balasubramaniam, S (1976)
The adenine analogue 4-aminopyrazolopyrimidine has been reported previously to reduce the hepatic secretion of plasma lipoproteins in rats, thereby lowering the plasma cholesterol level. In the current studies, reduction of the plasma cholesterol level by 90% in rats through the administration of aminopyrazolopyrimidine was found to be associated with a 5- to 30-fold increase in the activity of 3-hydroxy-3-methylglutaryl-coenzyme A reductase [mevalonate:NADP+ oxidoreductase (CoA-acylating), EC1.1.1.34] in kidney and lung. In both tissues, the enhanced activity of this microsomal enzyme was associated with a 3-fold elevation in the rate of cholesterol synthesis from either [14C]acetate or [14C]octanoate. Comparable increases were not observed in the activities of several other microsomal enzymes or in the rates of [14C]acetate incorporation into saponifiable lipids or CO2. When administration of 4-aminopyrazolopyrimidine was terminated, plasma cholesterol levels rose and 3-hydroxy-3-methylglutaryl-coenzyme A reductase activity declined in the kidney in a reciprocal manner. These data are consistent with the hypothesis that the low levels of 3-hydroxy-3-methylglutaryl-coenzyme A reductase activity and cholesterol synthesis that are normally observed in certain nonhepatic tissues of the rat are due to an active form of feedback regulation mediated by cholesterol carried in plasma lipoproteins.